Explore BrainMass

Explore BrainMass

    Algebra with Indicies

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    Given that S=(R+D)^(1/3) and T=(R-D)^(1/3) where
    D= square root(R^2+Q^3), show that ST=-Q

    © BrainMass Inc. brainmass.com March 4, 2021, 5:52 pm ad1c9bdddf

    Solution Preview

    Left hend side:
    ST = (R+D)^(1/3) * (R-d)^(1/3)
    => ST = [(R+D)*(R-D)]^(1/3)
    => ...

    Solution Summary

    An equality is proven. The proof is concise.